1974
DOI: 10.1159/000271353
|View full text |Cite
|
Sign up to set email alerts
|

Sufficiency of Reward and Allocation Behavior

Abstract: The present research investigated the effect of sufficiency of reward on the principles that elementary school children employ to allocate rewards to others. Results indicated that Justice children allocated a smaller proportion of reward to the winner of a game when they were distributing insufficient and oversufficient quantities of reward than when they were distributing a sufficient quantity of reward. Results also indicated that kindergarten children allocated significantly less reward to the winner than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…Sex had no effect on reward allocation in the present study, as was the case in some prior studies (Coon et al 1974;Lane & Coon 1972;Lerner 1974). Other research, however, indicates that males have a greater preference for equity than females (Benton 1971;Leventhal & Anderson 1970;Leventhal et al 1973), and on one occasion the reverse of that was found (Lerner 1974).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Sex had no effect on reward allocation in the present study, as was the case in some prior studies (Coon et al 1974;Lane & Coon 1972;Lerner 1974). Other research, however, indicates that males have a greater preference for equity than females (Benton 1971;Leventhal & Anderson 1970;Leventhal et al 1973), and on one occasion the reverse of that was found (Lerner 1974).…”
Section: Discussionsupporting
confidence: 53%
“…Lerner (1974), however, found that kindergarten-age supervisors generally favored equality and fifth-grade supervisors were about equally divided between those favoring equality and those favoring equity. Coon, Lane, and Lichtman (1974) employed a group administration procedure in their superThe research was based on an honors thesis submitted by the senior author to the Department of Psychology of Indiana University. Requests for reprints should be sent to Jerome M. Chertkoff, Department of Psychology, Indiana University, Bloomington, Indiana 47401.…”
mentioning
confidence: 99%
“…Past research (e.g., Coon, Lane, & Lichtman, 1974;Lane & Messe, 1972;Miller, 1977) has demonstrated that reward-distribution behavior is affected by internal standards of fair pay. It follows, then, that the established sense of own equity would directly influence people's evaluations of the fairness of their pay.…”
Section: Studymentioning
confidence: 99%
“…Lane & Messe (1972) previously obtained estimates of perceived 'fair pay' for the kind of work preconditions to be employed in their study and asked subjects to divide a total store of outcomes which varied in the sufficiency with which those standards could be met (see Coon, Lane & Lichtman, 1974, for more research using this paradigm). Outcomes were divided equally (and thus equitably, since work performances were equal) only where outcomes were sufficient.…”
Section: Ronald L Colienmentioning
confidence: 99%